A Within-Subjects, Within-Task Demonstration of Intact Spatial Reference Memory and Impaired Spatial Working Memory in Glutamate Receptor-A-Deficient Mice - Schmitt, Wolfram B; Deacon, Robert M. J; Seeburg, Peter H; Rawlins, J. Nicholas P; Bannerman, David M (The Journal of neuroscience, 2003)
Gene-targeted mice lacking the AMPA receptor subunit glutamate receptor-A (GluRA) (GluR1) and wild-type controls were compared on a radial-maze task in which the same three of six arms were always baited, but in which the rewards of milk were not replaced within a trial. This procedure allowed not only a within-subjects but also a within-trials assessment of both spatial working memory (WM) and reference memory (RM) in GluRA-/- mice, using identical spatial cues. In experiment 1, the GluRA-/- mice made more WM and RM errors during task acquisition. However, separate groups of GluRA-/- and wild-type mice (experiment 2) acquired a purely RM version of the task at a similar rate, using a paradigm with which it was not possible to make WM errors (doors prevented mice from re-entering an arm that they had already visited on that trial). In contrast, mice with hippocampal lesions were dramatically impaired. These results are consistent with the possibility that the WM impairment in the GluRA-/- mice during experiment 1 produced interference that disrupted RM acquisition. A WM component was therefore introduced after RM acquisition in experiment 2 (i.e., the mice were no longer prevented from re-entering a previously visited arm). The GluRA-/- mice now made considerably more WM errors than did wild-type mice, but simultaneously, RM was only mildly and transiently impaired. These experiments provide additional evidence of a selective spatial WM deficit coexisting with intact spatial RM acquisition in GluRA-/- mice, suggesting that different neuronal mechanisms within the hippocampus may support these different kinds of information processing.